Some Notes on the Surrogate Production Function - McIntosh, J. (Review of Economic Studies, 1972)
Journal Article Some Notes on the Surrogate Production Function Get access James McIntosh James McIntosh London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 505–510, https://doi.org/10.2307/2296520 Published: 01 September 1972